Reaksi Pasar Modal Indonesia Terhadap Peristiwa Pemilihan Gubernur DKI Jakarta Putaran II 2012 (Event Study pada Saham Anggota Indeks Kompas 100) - Wardhani, Laksmi Swastika; Djazuli, Atim (Jurnal Ilmiah Mahasiswa FEB, 2012)
Abstract: This research is an event study that aims to discover whether there is any empirical evidence of the Indonesia capital market reaction to one of the political events in the country, namely Jakarta Governor Election 2012 Round II, by using indicator abnormal return and trading volume activity. Population in this research is the stocks included in the Kompas 100 index on the Indonesia Stock Exchange, and the data used in this research are secondary data consists of daily stock prices, daily share trading volume, and daily stock prices index during the five days before, one day at the time of, and five days after the event. Statistical tool used to test the hypothesis is t-test and Wilcoxon Signed Rank Test. T-test calculation results indicate that there are significant positive value of abnormal return at a few days around the event date, which means the market responds to this event as a good news. While the results of Wilcoxon Signed Rank Test prove that there is a significant difference between the average abnormal return in the period at the time of-after the event, but not significant in the period before-at the time of and the period before-after the event. The results of Wilcoxon Signed Rank Test also shows that there are significant differences between the average trading volume activity in the period before-at the time of and the period at the time of-after the event, but not significant in the period before-after the event. Keywords: Capital Markets, Event Study, Abnormal Returns, Trading Volume Activity